An Overview on Microneedle Technology: Superior Pharmaceutical Transdermal Delivery Forms - Ganguly, Paramita; Saha, Puja; Khawas, Sourav; Chatterjee, Sandip; Patel, Arvind Kumar; Pati, Prangyan Paramita (International Journal of Pharmaceutical Investigation, 2026)
Microneedles, first introduced in 1976, address these limitations by creating tiny, non-invasive channels that enhance drug penetration through the skin. Transdermal Drug Delivery (TDD) is a less intrusive approach that bypasses first-pass metabolism and enables self-administration. However, the Stratum corneum, the skin’s outermost layer, acts as a strong barrier, restricting drug absorption. While hypodermic needle injections are effective, they are invasive, painful, and produce hazardous waste. Moreover, they are less efficient for vaccine delivery, as they administer the drug into muscle rather than the skin. Microneedles have proven effective in enhancing the delivery of various drugs, including vaccines and protein therapeutics, and can be designed with different materials and structures to maximize performance. The success of pharmaceuticals depends not only on the drug itself but also on the delivery method. While oral administration is convenient, it presents challenges for certain drugs due to low absorption or degradation. Microneedles provide an innovative alternative, enabling the efficient delivery of both small molecules and large proteins with minimal pain and high bioavailability. As a breakthrough in drug delivery technology, they offer a promising solution to the limitations of traditional methods.
Keywords: Microneedles; Transdermal; Bioavailability; Skin; Drug delivery; Efficacy